(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This paper examines the current innovative approaches in Uzbekistan’s agricultural sector aimed at ensuring food security. Special attention is given to the implementation of digital technologies, biotechnology, and precision agriculture methods. Achievements, challenges, and future prospects for agrotechnology in the face of climate and economic challenges are analyzed. The study concludes that comprehensive support for innovation at both the state and private levels is essential.